FSAN OAN-WG and future issues for broadband optical access networks. - Maeda, Y. (IEEE Communications magazine)
Network operators are aiming to provide a broadband access network to facilitate the next-generation telecom services. They have established the Full Services Access Networks (FSAN) group in order to find the best way to achieve early and cost-effective deployment of broadband optical access systems. They concluded that a single worldwide broadband access system should be investigated in the FSAN and then standardized in the international standards bodies such as the ITU-T. This article outlines the FSAN organization and the study targets for its Optical Access Network working group, and some key future study issues in terms of optical distribution network requirements and the required system functionalities of the B-PON system. It also describes its standardization strategy and the interaction between the FSAN and ITU-T